Economic analysis of harvesting coffee using repeat operations - Santinato, Felipe; Ruas, Renato Adriane Alves; da Silva, Rouverson Pereira; Duarte, Alino Pereira; Santinato, Roberto (Coffee Science - ISSN 1984-3909, 2015)
Despite the mechanized harvest of coffee is more economical than manual harvesting in general, it is not able to fully replace the workforce, especially in high crop load. One of the ways to reduce the cost of production of coffee is to find ways of enabling the full mechanization of the harvest. Therefore, the aim with this study was to perform economic analysis of mechanized harvest of coffee using repeated operation of the harvester own or ment, in the Cerrado Mineiro region. We analyzed the cost of mechanized harvesting with a combine six operations and manual harvesting, using own and rented harvester farming in high-load and intermediate in the Cerrado Mineiro, Minas Gerais, Brazil. We used a randomized block design with four replications. It was found that in high load crops (121,54 bags of coffee benefited ha-1), the use of three operations eithen harvester, own or ment or is the most suitable choice of harvest (R$ 3.975,36 and 4.775,03 ha-1, respectively). In farming intermediate load (50,78 bags of coffee benefited ha-1), the use of three operations of the combine when it is proper and two pass when it is rented is recommended (R$ 2.543,97 and 2.783,60 ha-1, respectively).